Strandveld Sanctuary Striving for Balance: the role of agriculture in the future urban environment. Can urban agriculture play a role in making our cities more sustainable and resilient? - Grobbelaar, Charleen (School of Architecture, Planning and Geomatics, 2021)
The study started off in the form of an investigation into the global phenomenon of declining africultural land. Several case studies with different approaces were overlaid onto the project site and from there the concept of a socio-ecological corridor network was born. The idea to create corridors that stretches through the urban fabric, connecting areas of biodiversity as well as potential production sites. Creating social and economi-cal benefits for the region. 1 Having deduced that the area of interest lay to the east of the PHA an investigation of the existing models of intervention in this specific area was undertaken. A number of urban agricultural projects run by independent non-profit organizations were identified. Focussing on community gardens, these projects were then researched and mapped. Focussing on the SEED organization, a basic model of intervention was developed. The deduction was that it is very difficult to compete with the scale of production of the PHA on a financial level. In the search for another model the Herbanisation project offered a different scenario. Indigenous plants with traditional medicinal qualities were planted as part of a open-access street garden. This was done in response to a PHO study that highlighted the economic value of the trade in these plants as well as the social problem of access to plant material that were traditionally freely available, but are now typically found within conservation areas, making forraging an illegal activity. By creating street gardens not only were these materials now freely available to the wider public,